REGIONAL ECOTURISM ON THE TERRITORY OF NORTH BACKA–COMMUNITY OF SUBOTICA - Čordaš, Robert (Economics of Agriculture, 2006)
Community Subotica encloses by its territory four protected natural estates but with different protection grades – international, republic and communal. One of them is The Desert of Subotica («Subotička peščara») as the area with exeptional nature eminence, then special reservations of nature – Lake Ludas («Ludaško jezero») and Heaths of Selevenia (« Selevenjske pustare»), and the natural park Palic (Palić). These protected natural estates are internationaly exepted. Exploitation and reservation areas with remarkable values, same as introducing those in interest for protected natural estates, should happen on principles education and giving informations to tourists and to local population. Beside this, the guardian of protected natural estates determines the régim of exploitation.